Evaluation of the effectiveness of the psychocorrection program for patients with newly diagnosed oncological pathology - Stanovskyi, Богдан (Psychosomatic Medicine and General Practice, 2023)
Abstract Еhe article presents the author's vision of the problem of providing psychological assistance to cancer patients in the process of consultative interaction and complex psychocorrective influence. There are outlined relationships between coping strategies and psychological well-being of cancer patients. There was compared the impact of standard psychological interviews to complex psychocorrective measures developed on the basis of data obtained during the first stage of the study. There were found changes in the psycho-emotional state, the level of adaptation to the disease and the quality of life of the patients, based on quantitative and qualitative psychodiagnostic methods. There has been established the specific elements of the psychocorrection program, which are the most effective for improving the psychological state and adaptation of patients, have been identified, as the interaction of these elements with the individual characteristics of each research participant. There were demonstrated significant improvements in quality of life indicators and a decrease in the feeling of helplessness among the participants of the research group. As a result of the obtained results, it was established that psychological correction is an important component in a comprehensive approach to the treatment and rehabilitation of patients with oncological diseases. There was emphasized the need for further implementation and development of psychocorrective programs to improve the quality of life of cancer patients and ensure their effective psychoemotional support. There has been proven the importance of integrating psychological support into the general plan of treatment and rehabilitation of cancer patients. Conclusions Based on the results of the data analysis, important conclusions can be drawn regarding the positive impact of psychological correction on the quality of life and reducing the feeling of helplessness among the study participants. It was found that the participants of the research group, who underwent complex psychocorrective interventions, demonstrated a significant improvement in "Quality of life" indicators and a decrease in the feeling of "Helplessness" compared to the control group. This indicates the importance of psychological support in the complex treatment and rehabilitation of cancer patients. It is worth noting that the conduct of such studies has certain methodological limitations, in particular, in relation to the selection of participants and the assessment of the long-term effects of psychocorrective interventions. Therefore, in order to deepen the understanding of the studied phenomena, further studies with a larger number of participants and longer observation of their condition are needed.